Lack of coupling between onset of giant transformation and genome endoreduplication in the mural trophectoderm of the mouse blastocyst. - Gardner, R; Davies, T (1993)
Prominent among the various types of cell that differentiate from the trophectoderm of the mouse blastocyst are trophoblastic giant cells. Repeated endoreduplication of the genome accompanies the growth of these cells, which have been shown to be polytene rather than polyploid. Early stages in giant transformation have been examined, mainly in the mural trophectoderm of the implanting blastocyst which gives rise to the primary trophoblastic giant cells. One confusing issue is whether these early stages include the onset of endoreduplication of the genome. This issue has been addressed in the present study by comparing the DNA content of nuclei in isolated trophectoderm and ICM tissue rather than, as previously, by relating measurements on air-dry preparations of entire blastocysts to those of adult liver. The results, particularly those from delayed and reactivated blastocysts, show that genome endoreduplication is not an obligatory early event in the transformation of mural trophectoderm cells.